2013
DOI: 10.1111/phn.12082
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Cornerstones of Public Health Nursing in Norway and in the United States

Abstract: The values and beliefs represented in the different modified cornerstones based on Norwegian community nursing practice capture the essence of public health nursing in Norway. The similarities between the two countries show that nurses have much in common, despite different health and governmental systems and laws.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 13 publications
(15 reference statements)
0
43
0
Order By: Relevance
“…In contrast to public health nursing services in the United States, PHNs in Norway focus only on health promotion and prevention work for families, youth, and children. Their attitudes and values, as well as their focus on health promotion and prevention are shared with PHNs across national borders (Glavin et al, ). PHNs intervene at all levels—individual/family, community, and systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast to public health nursing services in the United States, PHNs in Norway focus only on health promotion and prevention work for families, youth, and children. Their attitudes and values, as well as their focus on health promotion and prevention are shared with PHNs across national borders (Glavin et al, ). PHNs intervene at all levels—individual/family, community, and systems.…”
Section: Discussionmentioning
confidence: 99%
“…Although differences in public health nursing between Norway and the United States include both the focus of practice and structure of educational preparation, an analysis of values foundational to public health nursing revealed that the Cornerstones of Public Health Nursing, or PHN core beliefs and values, are similar for PHNs in the United States and Norway (Glavin, Schaffer, Halvorsrud, & Kvarme, ). PHNs in both countries identified important themes of core beliefs and values as: (a) promotion of health and prevention of disease; (b) holistic care including consideration of living conditions; (c) collaboration with clients, government, and health care organizations; (d) caring relationships; and (e) independence in public health nursing work.…”
Section: Introductionmentioning
confidence: 99%
“…Providing support to the consulter directly and working as a member of the administrative organization coexisted. This was similar to “Although Norwegian nurses were being guided by laws and municipalities' priority, they prioritized patient needs” (Glavin, Schaffer, Halvorsrud, & Kvarme, ). However, the identity of this study confirmed conflicts in addition to coexistence.…”
Section: Discussionmentioning
confidence: 80%
“…Thus, in addition to the provision of primary healthcare, the PHN is charged with the responsibility of reporting "inadequate" and harmful parenting to the Child Protection Service (Andrews, 2003). Notably, Norwegian PHNs complete a 1-year certificate in public health nursing after finishing their baccalaureate nursing program (Glavin, Schaffer, Halvorsrud, & Kvarme, 2014).…”
Section: Primary Healthcare Services (Phcs)mentioning
confidence: 99%